The impacts of consumer-funded renewable support schemes in the UK: From the perspective of consumers or the electricity sector? - Jing Shao (Renewable and Sustainable Energy Reviews, 2023)
Increased renewable electricity reduced electricity prices but the costs of consumer-funded support schemes were added to utility bills. Previous studies compared these two components to understand the impacts on consumers. This paper constructs a framework for the electricity sector and provides a new angle to examine the impacts of renewable support schemes on consumers and the sector, respectively. Any negative gain to consumers was offset by the positive gain received by renewable generators (and suppliers), leaving the sector unaffected. In contrast, the increase in renewable electricity brought positive gain to the sector as a whole through reduced fossil fuels imports and greenhouse gas (GHG) emissions. We examine the structural change in the generation mix from 2006 to 2020 in the UK and suggest that wind generation replaced coal-fired generation rather than gas-fired generation on the longer horizon. Therefore, using coal-related coefficients and a contribution share of 38.6% for renewable subsidies, we suggest that wind generation supported by the RO scheme brought positive net gain to the sector, exceeding £800 million per annum in 2018–19 and 2019–20. Therefore, the discrepancy in payoffs from the perspective of consumers and the sector imposed a difficult challenge for policymakers, as criticism would be raised if the analysis was done on consumers only.